Exploring Leadership Roles and Performance Dynamics in Regional Public Financial Institutions - Najeminur, Najeminur; Anugrah, Andi (Pattimura University, 2026)
This study examines the role of organizational leadership in enhancing employee performance within a local government financial management institution in Indonesia. Specifically, it analyzes how the leadership role of the agency head influences the performance of civil servants at the Regional Financial and Revenue Management Agency (BPKPD) of Wajo Regency. Employee performance in public sector organizations is a critical determinant of service quality, institutional effectiveness, and public accountability. However, leadership challenges, limited motivation, and organizational constraints often hinder optimal performance in local government institutions. This research adopts a qualitative descriptive approach to obtain an in-depth understanding of leadership practices and their impact on employee performance. Data were collected through in-depth interviews, direct observation, and document analysis involving key informants, including the agency head, structural officials, staff members, and community representatives. The analysis focuses on leadership roles such as directive, participative, and delegative leadership, as well as key performance indicators including work quality, work quantity, timeliness, efficiency, and teamwork. The findings reveal that the agency head plays a significant role in improving employee performance through clear direction, effective communication, participatory decision-making, and exemplary leadership behavior. Supportive factors such as employee development, recognition, and effective communication contribute positively to performance improvement. Conversely, inhibiting factors include inconsistent time discipline, limited trust, and insufficient empathy in certain leadership situations. Overall, effective leadership is shown to be a crucial element in strengthening employee performance and organizational effectiveness in local public financial management institutions. The study contributes to the literature on public sector leadership by providing empirical insights from a local government context in Indonesia.